大學多元入學制度：學生家庭社經背景與學業成就之比較 Multi-Channel College Entrance System: Relationship between Family Background, Academic Achievement and Entrance Channels - 田芳華 Fang-Hua Tien; 傅祖壇 Tsu-Tan Fu (National Taiwan Normal University, 2009)
本文分析不同入學管道之大學生社經背景差異，並比較其學業成就。研究採問卷調查蒐集資料，調查母體為十二所大學之大一學生，並運用多項勝算對數模型和區間迴歸進行資料分析。研究發現為：一、在考慮性別、父母親籍貫、父親教育程度和職業及領域的情形下，母親教育程度較高者經由個人申請管道入學之機率較考試分發入學的機率大；二、當其他變項條件相同時，與攻讀人文社會領域者相比，攻讀自然理工領域者經個人申請或學校推薦管道入學的可能性較考試分發高；三、在控制性別、家庭社經地位、領域、公私立學校和學習主動性後，個人申請和推薦入學者的學業表現比考試分發者來得好。 Purposes of this research are: (1) Analyzing differences of family background among students who were admitted to colleges via different entrance channels; (2) Comparing academic achievement of college students who are enrolled via different entrance channels. A survey was conducted. The survey population is defined as the first year college students enrolling in twelve universities. Statistical methods employed in this study include multinomial logit regression and interval regression. The main findings are: (1) After controlling for the effects of gender, father's ethnicity, mother's ethnicity, father's occupation, father's education, and the respondents' major, students of better educated mother tend to have higher chances of entering colleges via applying for admissions rather than taking entrance examination. (2) Holding other variables constant, the odds of applying for admissions to enter college compare to taking united entrance examination channel are higher among natural science and engineering students than humanities and social sciences students. (3) After considering the effects of gender, family socioeconomic status, majors, public or private university controls, and learning habits, college freshmen who entering colleges via "individual-apply" channel or "high school recommend" channel perform better academically in the first year than those who were enrolled by taking united entrance examination channel.